ANALYSIS OF CONSUMER PERCEPTIONS IN USING DIGITAL WALLETS - Fitrianingsih; Winda Clara Hutabarat; Rizka Izmi Nur; Adinda Lubis; Juwita Samaria Manurung (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
This research conducted on STIE Bina Karya Tebing Tinggi students, it can be concluded that the influence of perceptions about security and speed in digital wallet applications greatly influences digital wallets and plays an important role in increasing user adoption and loyalty, as well as influencing the success of digital wallets in market. Consumer perception of the level of security offered by digital wallets is also very important. When consumers feel that their transactions are safe and personal data is protected, they tend to be more trusting and loyal to the digital wallet service.